TO ESTIMATE THE FRICTIONAL FORCES AT THE POINTS OF START AND STOP OF THE ARMATURE OF THE RELAY - Razgonov, O. P.; Adreevskykh, O. V.; Bondarenko, B. M.; Bezrukavyi, D. O. (Science and Transport Progress, 2007)
The article considers issues of electromagnetic compatibility of traction network with the rail circuits. A mathematic model is elaborated for evaluation of distribution of harmonics of traction current on the length of feeder zone and determination of the value of stray currents. The results of modeling are represented for 50 and 100 Hz harmonics of return traction current.